IoT Based Covered Agriculture Monitoring and Control System with Smart Sensing and Forwarding Algorithm - et. al., Hussain Saeed Hassan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Internet of Things (IoT)-based monitoring and control device model can be used on farms. The proposed systems play an important role in data collection for the tracking system, as well as signal transmission to actuators in the control process. On top of this situation, IoT concept was implemented to link devices through the Internet and enable user access to knowledge. This device allows users to save money on supplies, cut costs, and monitor the output process on the field. The processed data will be sent to the monitoring system via MQTT with QoS level 2. Sensing and forwarding algorithm (SFA) was developed to reduce the power consumption of the data collection and processing unit. The obtained results show that the proposed algorithm has save about enhanced the system power consumption about 65% when compared to non-SFA operation.